General practitioners' (GPs) experience, attitudes and needs on clinical genetic services: a systematic review - Ong, Cheryl Siow Bin (2023)
Objective: The proliferation and growing demands of genetic testing are anticipated to revolutionise medical practice. As gatekeepers of healthcare systems, general practitioners (GPs) are expected to play a critical role in the provision of clinical genetic services. This paper aims to review existing literature on GPs' experience, attitudes and needs towards clinical genetic services. Design: A systematic mixed studies review of papers published between 2010 and 2022. Eligibility criteria: The inclusion criterion was peer-reviewed articles in English and related to GPs' experience, views and needs on any genetic testing. Information sources: The PubMed, PsycINFO, Cochrane, EMBASE databases were searched using Mesh terms, Boolean and wildcards combinations to identify peer-reviewed articles published from 2010 to 2022. Study quality was assessed using Mixed Methods Appraisal Tool. Only articles that fulfilled the inclusion criteria were selected. A thematic meta-synthesis was conducted on the final sample of selected articles to identify key themes. Results: A total of 62 articles were included in the review. Uncertainty over GPs' role in providing genetic services were attributed by the lack of confidence and time constraints and rarity of cases may further exacerbate their reluctance to shoulder an expanded role in clinical genetics. Although educational interventions were found to increasing GPs' knowledge and confidence to carry out genetic tasks, varied interest on genetic testing and preference for a shared care model with other genetic health professionals have resulted in minimal translation to clinical adoption. Conclusion: This review highlights the need for deeper exploration of GPs' varied experience and attitudes towards clinical genetic services to better facilitate targeted intervention in the adoption of clinical genetics.